TEACHER’S BELIEFS ON USING CODE SWITCHING IN RELATION TO BUILDING STUDENTS’ SOCIAL EMOTIONAL COMPETENCE - L A Suganda; I Petrus; Zuraida Zuraida; D Kurniawan; Mardiana Mardiana (Sriwijaya University Learning and Education International Conference, 2018)
This study investigated the phenomenon of code switching or the use of English and Indonesian as a medium of instruction used by the English as a Foreign Language teacher in her classroom discourse. It was conducted in a seventh grade English class at one secondary school in South Sumatera, Indonesia. This case study focuses on revealing the teacher’ perceptions towards her use of code switching in relation to build her students’ social emotional competence. The teaching and learning processes in the classroom were recorded and transcribed to explore the occurrence of code switching in the classroom discourse. A face to face semi-structured interview with the teacher was held and analysed to see her perception and purposes of doing code switching in the class. The study results indicated that the switching between English and Indonesian in the EFL classrooms plays a positive role in building the students social emotional competence during the teaching and learning process. The main reason the teacher uses code switching is to have a better communication with her students while transferring the material or topic of discussion as well as to remind and motivate them to have higher social emotional competence in their English learning process.